A participação dos conselheiros estaduais de saúde de Minas Gerais no enfrentamento à pandemia de COVID-19 - Cristiane Aparecida Costa Tavares (2023)
Public health in Brazil is a complex issue, both from the point of view of caring for the population and managing systems and services. The health area was regulated in 1990 by Law No. 8.080, which, among other elements, indicated community participation in the formulation and definition of public health policies as a guideline. During this same period, in a context of political openness and re-democratization of the country, councils were established as one of the main spaces for the exercise of participation and social control aimed at the implementation of public policies in all spheres of government. In the area of health, in particular, councils have participated continuously in the management of public policies, overseeing the application of resources, controlling the execution of programs, monitoring economic and financial aspects, analyzing the health plan and monitoring the implementation of the guidelines of health conferences at each level of government. In March 2020, the World Health Organization declared the COVID-19 pandemic, caused by the new coronavirus, constituting a public health emergency of international importance. In a scenario, in which several emergency measures needed to be taken, seeking to face the health crisis situation, the research aimed to understand the participation of state health advisors in Minas Gerais in facing the COVID-19 pandemic. This is a case study, with a qualitative and interpretative approach. The research participants were the counselors (permanent members) of the board of directors of the State Health Council. For data collection, document analysis techniques were used, holding a focus group with the counselors and interviews with a semi-structured script with the vice-president. president, using data triangulation. Content analysis was used for data analysis. The research was approved by the UFMG Ethics Committee, through Opinion nº 5,797,773 and authorized by the board of directors of the State Health Council, according to Official CES-MG nº 241. Of the eight effective members, who made up the board of directors of the State Health Council, six participated in the proposed interventions. One was a representative of public authorities and five were representatives of civil society, of these, four were representatives of users of the Unified Health System and two represented health workers. The profile of these participants indicated that the majority were male, black or mixed race, residing in Belo Horizonte, over 40 years old, with complete secondary education, remuneration of one to three minimum wages and with more than four years of experience at the State Health Council (one working for 55 years). The research results identified the active work of state health advisors in Minas Gerais during the COVID-19 pandemic, who sought to meet virtually, facing obstacles from technological platforms since the beginning of the pandemic, when the situation was still uncertain; financing problems that made it impossible for the counselors of the State Health Council to perform better, due to the impossibility of using the financial budget that is guaranteed by the Annual Budget Law; joint action with the Public Ministry on two occasions when the state of Minas Gerais requested a statement on a specific topic.